Color Dominance in Artwork by Children with ADHD: Dominasi Warna pada Karya Anak dengan GPPH - Rahmawati, Indira Ismi; Wati, Tri Linggo (Indonesian Journal of Education Methods Development, 2024)
General Background: Color is a fundamental element in children's drawings, reflecting their emotions and experiences. Specific Background: Children with special needs, particularly those with Attention Deficit Hyperactivity Disorder (ADHD), may exhibit unique patterns in color usage, influenced by their perceptions and memories. Knowledge Gap: Limited research exists on how color dominance in drawings can provide insights into the thoughts and feelings of children with ADHD. Aims: This study aims to identify the dominant colors used by children with ADHD in their drawings, enhancing educators' understanding of these children's emotional landscapes. Results: Employing a qualitative phenomenological approach, data were gathered through observation, interviews, and documentation, with validity assessed via source triangulation. The findings reveal that children with ADHD predominantly select darker colors, such as black, dark blue, and brown, which correspond to significant past experiences or events they have encountered. Novelty: This research contributes new insights into the relationship between color choice and the emotional expression of children with ADHD. Implications: Understanding color dominance in their artwork can aid educators in recognizing and addressing the emotional and psychological needs of these children, fostering a more supportive learning environment. Highlights: Color Selection: Children with ADHD predominantly choose dark colors in their drawings. Emotional Reflection: Color dominance reflects significant past experiences and emotions. Qualitative Insights: The study uses a phenomenological approach to analyze children's artwork. Keywords: color dominance, ADHD, children's drawings, emotional expression, qualitative research